Microbial and Transcriptomic Profiling Reveals Diet-Related Alterations of Metabolism in Metabolic Disordered Mice - Zhu, Weize; Hong, Ying; Li, Yue; Li, Yan; Zhong, Jing; He, Xiaofang; Zheng, Ningning; Sheng, Lili; Li, Houkai (Frontiers in Nutrition, 2022)
Metabolic disorders are the prelude of metabolic diseases, which are mainly due to the high energy intake and genetic contribution. High fat diet (HFD) or high sucrose diet is widely used for inducing metabolic disorders characterized with increased body weight, insulin resistance, hepatic steatosis and alteration of gut microbiome. However, the triangle relationship among diets, gut microbiome and host metabolism is poorly understood. In our current study, we investigated the dynamic changes of gut microbiota, and host metabolism in mice that were fed with either chow diet, HFD or chow diet with 30% sucrose in drinking water (HSD) for continued 12 weeks. The gut microbiota was analyzed with 16S rDNA sequencing on feces. Hepatic gene expression profile was tested with transcriptomics analysis on liver tissue. The host metabolism was evaluated by measuring body weight, insulin sensitivity, serum lipids and expression of proteins involved in lipid metabolism of liver. The results showed that HFD feeding caused more serious characters in metabolic phenotypes including body weight gain, insulin resistance, and hepatic steatosis compared to HSD feeding mice. 16S rRNA gene sequencing showed that HFD rapidly and steadily suppressed species richness, altered microbiota structure and function, and increased the abundance of bacteria responsible for fatty acid metabolism and inflammatory signaling. In contrast, HSD had minor impact on the overall bacteria structure or function but activated microbial bile acid biosynthesis. Fecal microbiota transplantation suggested that some metabolic changes induced by HFD or HSD feeding were transferrable, especially in WAT weight and hepatic TG contents that were consistent with the phenotypes in donor mice. Moreover, transcriptomic results showed that HFD feeding significantly inhibited fatty acid degradation and increase inflammation, while HSD increased hepatic de novo lipogenesis and inhibited primary bile acid synthesis alternative pathway. In general, our study revealed the dynamic and diversified impacts of HFD and HSD on gut microbiota and host metabolism.